2007
DOI: 10.1007/s11244-007-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic phenomena of SCR-catalysts containing Fe-exchanged zeolites – experiments and computer simulations

Abstract: The dynamic behaviour of the NO SCR-reaction on Fe-exchanged zeolites was investigated by the transient response method (TRM). The results were used to develop a mathematical model for catalysts containing Fe-exchanged zeolites capable of describing the dynamic phenomena observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…Vanadia supported on titania [1][2][3][4][5] and Cu- [6][7][8][9][10][11][12][13][14] and Fe-exchanged [15][16][17] zeolites have been extensively studied for this reaction. A major advantage of Cu/zeolites is that they exhibit a high level of activity at low temperature [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadia supported on titania [1][2][3][4][5] and Cu- [6][7][8][9][10][11][12][13][14] and Fe-exchanged [15][16][17] zeolites have been extensively studied for this reaction. A major advantage of Cu/zeolites is that they exhibit a high level of activity at low temperature [18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gao et al [29] observed two regimes, below and above 250 • C with different activation energies for ammonia oxidation over Cu/SSZ-13, and suggested that this may be attributable to a change in the rate limiting mechanism or a change in the coordination of the Cu/ion catalytic centers resulting in different reactivity. There are several kinetic models available in the literature for different ammonia-SCR catalysts, like vanadia on titania [1][2][3][4][5], Cu/ZSM-5 [31][32][33][34], Cu/faujasite [35], Cu/Beta [36], Cu/CHA [37], HZSM-5 [38] and Fe/zeolites [15][16][17]39]. For Cu/zeolites, both detailed [32][33][34] and global kinetic models [13,31,40] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers deal with kinetic modelling of the NH 3 -SCR process over metal promoted zeolites [8,[13][14][15][16]. Some of them illustrate global models of the Standard SCR under steady state conditions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, only very few kinetic models consider the effects of the variation of the NO/NO 2 feed ratio and of transient operation. Malmberg et al [15] and Chatterjee et al [8] presented transient global models for NH 3 -SCR with NO over Fezeolite systems. Olsson et al [16] recently developed a global dynamic kinetic model for NO/NO 2 -NH 3 SCR over a Cu-ZSM-5 catalyst; however, ammonium nitrate formation (3) was not included in the kinetic scheme.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction was chosen as a test case due to its importance within the scope of modern exhaust gas aftertreatment technologies, such as the NO x storage reduction (NSR) [3,4], the selective catalytic reduction (SCR) [5,6], and the continuous regenerating trap (CRT) [7] technologies.…”
Section: Introductionmentioning
confidence: 99%